Sport and exercise medicine/physiotherapy publishing has a gender/sex equity problem: we need action now! - Cowan, S. M.; Kemp, J. L.; Ardern, C. L.; Thornton, J. S.; Rio, E. K.; Bruder, A. M.; Mosler, A. B.; Patterson, B.; Haberfield, M.; Roughead, E. A.; Hart, H.; To, L.; et al. (British Journal of Sports Medicine, 2023)
Objectives: We aimed to determine (1) the proportion of women authors overall, in first (lead) and last (senior) author positions, (2) the proportion of women research participants and (3) the association between women in first and/or last author positions and the proportion of women research participants in original research articles and editorials/opinion pieces in four sport and exercise medicine/physiotherapy journals.